Pacioli's Lens: God, Humanism, Euclid, and the Rhetoric of Double Entry - Sangster, Alan (The Accounting Review, 2018)
ABSTRACT This paper investigates why, in 1494, the Franciscan friar and teacher of mathematics, Luca Pacioli, published an instructional treatise describing the system of double entry bookkeeping. In doing so, it also explores the rhetoric and foundations of double entry through the lens of Pacioli's treatise. Recent findings on Pacioli's life and works, his writings, and the medieval accounting archives are combined to identify how he was inspired by his faith and his humanist beliefs to give all merchants access to the practical mathematics and the bookkeeping they required. The paper finds that Pacioli's teaching method was inspired by Euclid, his Franciscan education, and his humanist beliefs, and that Pacioli reveals a simplicity in the then-unrecognized axiomatic foundation of double entry that has been largely overlooked. The findings represent a paradigm shift in how we perceive Pacioli, his treatise, and double entry.